Synthesis, conformation and Hirshfeld surface analysis of benzoxazole methyl ester as a versatile building block for heterocycles. Issue 9 (September 2021) - Saeed, Aamer; Shabir, Ghulam; Hökelek, Tuncer; Flörke, Ülrich; Erben, Mauricio F.
Abstract: Solventless cyclocondensation of 2-aminothiophenol with thiourea afforded the benzo[ d ]oxazole-2-thiol (3a ) capable of existing also in the tautomeric form benzo[ d ]oxazole-2(3 H )-thione (3b ). Acylation with methyl chloroacetate in dry ethanol in absence of any base or catalyst selectively afforded the S -substituted ester 2-(methoxycarbonylmethylthio)benzo[ d ]oxazole (4a ) in preference to the corresponding N -substituted ester N -(methoxycarbonylmethyl)thioxobenzoxazole (4b ). Quantum chemical calculations were conducted to determine the conformational landscape and NBO population analysis showed the strong electronic delocalization via resonance interactions on the 2-mercaptobenzaxazole group. The anomeric effect and the occurrence of a 1, 4-S···O intramolecular interactions suggest the relevance of chalcogen bonding in the conformational preference. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H⋯H (33.2%), H⋯O/O⋯H (19.9%) and H⋯C/C⋯H (17.8%) interactions. Hydrogen bonding and van der Waals interactions are the dominant interactions in the crystal packing. Computational chemistry indicates that in the crystal, the C–H⋯O hydrogen-bond energy is 44.8 kJ mol −1 . Abstract : Molecular structure; benzo[ d ]oxazole-2(3 H )-thione; Hirshfeld surface analysis; Natural bond orbital.